Analisis Bibliometrik : Penelitian Literasi Digital dan Hasil Belajar pada Database Scopus (2009-2023) - Soraya, Septiany Maulani; Kurjono, Kurjono; Muhammad, Ilham (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
High digital literacy skills can make it easier for students to follow every learning process. Learning outcomes are one indicator of successful learning in the academic field. The purpose of this research is to look at the research landscape related to digital literacy and learning outcomes from the Scopus database, the method used is bibliometric analysis. The results of the study show that the number of publications related to digital literacy and learning outcomes increases every year from 2018 to 2022. The largest number of documents is in the United States, the highest number of documents is in institutions or universities "London school of economics and political science" with 281 citations, in the journal "Journal of information technology education: research" with 2 documents, then in the article with the highest number of citations, namely research conducted by (Falloon 2020). The second research focus is digital literacy, blended learning and technology. The third research focus is earning outcomes, digital technology and information literacy. The three research focuses above can be used as a reference for further researchers to determine the research theme. The keywords that became the new theme were digital story telling, blended learning, artificial intelligence, technology, critical thinking, and creative problem solving.